KEBUGARAN AEROBIK PEMAIN SEPAKBOLA PSIM YOGYAKARTA TAHUN 2014 - Subagyo Irianto (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2016)
This study is aimed to investigate aerobic fitness of PSIM Yogyakarta football players in 2014 and development of aerobic fitness of PSIM Yogyakarta football players in 2014. The research is a descriptive study. The subjects were all 26 PSIM football players who competed in the PSSI premier division competition in 2014. Data collection was conducted using documentation method by taking data from the PSIM Yogyakarta Administrative Staff. The instrument used in this study was a Balke 15-minute test run. Data was analysed using descriptive percentages. The results showed that: (1) aerobic fitness results before undergoing the training program are: (a) Perfect (0 player or 0%), (b) Very Good (0 player or 0%), (c) Good (0 player or 0%), (d) Fair (6 players or 23.07%), and (e) Poor (20 players or 76.93%); (2) aerobic fitness results after undergoing aerobic exercise program are: (a) Perfect (0 player or 0%), (b) Very Good (0 player or 0%), (c) Good (4 players or 15.75%), (d) Fair (12 players or 46.20%), and (e) Poor (10 players or 38.45%). There is a significant increase between Test I and Test II with the average value 2.9 ml.kg body weight per minute.Keywords: Aerobic fitness, football, Indonesia premier division leagueABSTRAKPenelitian ini bertujuan mengetahui kebugaran aerobik pemain sepakbola PSIM Yogyakarta tahun 2014 dan untuk mengetahui perkembangan kebugaran aerobik pemain sepakbola PSIM Yogyakarta tahun 2014. Desain penelitian adalah diskriptif. Subjek penelitian adalah seluruh pemain sepakbola PSIM yang berlaga pada kompetisi divisi utama PSSI tahun 2014 sebanyak 26 pemain. Metode pengambilan data dilakukan dengan metode dokumentasi yaitu mengambil data yang ada di Staf Administrasi PSIM di Yogyakarta. Adapun instrumen yang digunakan dalam penelitian ini adalah tes lari 15 menit dari balke. Untuk teknik analisis data dengan menggunakan deskriptif persentase. Hasil penelitian menunjukkan bahwa Kebugaran aerobik sebelum menjalani program latihan adalah: (a) Sempurna (0%), (b) Baik Sekali (0%), (c) Baik (0%), (d) Cukup 6 (23,07%), dan (e) Kurang 20 (76,93%). Kebugaran aerobik setelah menjalani program latihan adalah: (a) Sempurna 0 (0%), (b) Baik Sekali 0 (0%), (c) Baik 4 (15,75%), (d) Cukup 12 (46,20%), dan (e) Kurang 10 (38,45). Terdapat peningkatan secara signifikan dengan selisih nilai rerata antara Tes I dan Tes II sebesar 2,9 ml.kg.bb per menit.Kata kunci: kebugaran aerobik, sepakbola, divisi utama liga indonesia